Mental Health Status among Systemic Lupus Erythematosus (SLE) Patients at Tertiary Hospital in Malaysia - Mohd Haazik Mohamed; Sangaran Gopal; Idayu Badilla Idris; Azimatun Noor Aizuddin; Hazlina Mohd Miskam (Asian Social Work Journal, 2020)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease that can affect and cause damage to several human organs such as the skin, kidneys, muscles, joints, lungs, heart and brain. Uncontrolled relapses in SLE patients can lead to death. SLE patients and their families also face difficulties due to lack of information about the disease. Therefore, studies focused on the psychological aspects such as symptoms of anxiety and depression among SLE patients is still needed in Malaysia. Thus, this study investigated the psychological status of SLE such as the occurrence of anxiety and depression in SLE patients and its associated factors. A cross sectional study using the purposive sampling was carried out at University Kebangsaan Malaysia Medical Centre (UKMMC). Hospital Anxiety and Depression Scale questionnaires were used to occurrence of anxiety and depression respectively. Out of 150 SLE patients participated, 46.6% had anxiety while another 33.3% experienced severe depression. Anxiety and depression were significantly correlated with socio demographic factors such as gender (p = 0.006, p = 0.003 respectively), level of education (p = 0.028, p = 0.003 respectively), and monthly income (p = 0.008, p = 0.001 respectively). Overall, socio demographic factors have important influence on the occurrence of anxiety and depression in patients with SLE. Mental health issue among SLE patient in Malaysia should be taken into consideration by health care provider especially by medical social worker.